BUTTERFLY FLOWER TEA BAGS ARE A MOOD BOOSTER AND IMMUNE BOOSTER AS WELL AS A GOOD BUSINESS IDEA WHICH HAS THE POTENTIAL TO GENERATE ADDITIONAL INCOME - Agustina Dwi Prastanti; Rini Indrati; Mega Indah Puspita (Poltekkes Kemenkes Semarang, 2024)
The use of butterfly pea flowers in society is not yet widely known, so consumption of butterfly pea flowers is still low because many people do not know about the benefits of butterfly pea flowers as an immune booster. So it is necessary to increase the use of butterfly pea flowers so that they are easy to consume, one of which is by processing them into butterfly pea flower tea bags. The aim of carrying out this community service is to teach residents to process butterfly pea flowers into practical tea bags and package them into UMKM products that can provide additional income as a good business idea. The community service method is through lectures, discussions and direct practice. The community service element involves the head of the PKK RT, RW, and health cadres. The direct practice of processing butterfly pea flowers by the community produces results in the form of butterfly pea flower tea bags with attractive packaging and a PIRT business permit. This activity has succeeded in mobilizing residents to process butterfly pea flowers into tea bag products that are ready for consumption and marketing.